Comparison of real-world outcomes of adalimumab and infliximab for patients with ulcerative colitis in the United States. (2nd July 2016) - Sandborn, William J.; Sakuraba, Atsushi; Wang, Anthony; Macaulay, Dendy; Reichmann, William; Wang, Song; Chao, Jingdong; Skup, Martha
Abstract: Objective : We compared the real-world effectiveness of initiating adalimumab and infliximab among patients in the US who were naïve to tumor necrosis factor (TNF) inhibitors.Methods : A retrospective chart review was conducted to evaluate the real-world effectiveness among adults with ulcerative colitis (UC) initiating adalimumab or infliximab. Charts of patients with UC were abstracted by treating physicians (randomly selected from a nationally representative panel) in April 2014. Patient eligibility criteria included: adalimumab or infliximab initiation on/after 1 October 2012; no prior anti-TNF therapy, history of Crohn's disease, or colectomy; and ≥6 months of follow-up. Information on clinical outcomes (partial Mayo score, remission rate, physician global assessment (PGA), stool frequency, and rectal bleeding) and treatment patterns (dose escalations, discontinuations, switches, and treatment augmentations) were retrospectively reported by treating physicians. Kaplan–Meier curves and multivariate Cox proportional hazards regression models were used to assess the time to clinical outcomes and treatment changes for each therapy.Results : Overall, 170 physicians participated, contributing data on 380 and 424 patients who initiated adalimumab and infliximab, respectively. Baseline clinical characteristics were similar between groups. Both adalimumab- and infliximab-treated patients showed substantial improvements from baseline to follow-up in effectiveness measures; results of these measures were similar between the adalimumab and infliximab cohorts. Time to remission ( p = 0.5241), no rectal bleeding ( p = 0.7648), normal stool count ( p = 0.9941), and normal PGA ( p = 0.7697) showed no significant differences between therapies in unadjusted and adjusted comparisons. Unadjusted and adjusted time to event analysis of discontinuation ( p = 0.7151), dose escalation ( p = 0.6310), treatment augmentation ( p = 0.1209), and switching ( p = 0.7975) showed no significant differences between the two cohorts.Limitations : Retrospective, observational design.Conclusions : Adalimumab and infliximab were similarly effective in the treatment of moderate-to-severe UC in the real-world clinical setting.